Influence of Winemaking Practices on the Characteristics of Winery Wastewater and Water Usage of Wineries - Conradie, A.; Sigge, G.O.; Cloete, T.E. (South African Journal of Enology and Viticulture, 2016)
The winemaking industry produces large volumes of wastewater that pose an environmental threat if not treated correctly. The increasing numbers of wineries and the demand for wine around the world are adding to the growing problem. The vinification process includes all steps of the winemaking process, from the receipt of grapes to the final packaged product in the bottle. To fully understand all the aspects of winery wastewater it is important to know the winemaking processes before considering possible treatments. Winemaking is seen as an art and all wineries are individual, hence treatment solutions should be different. Furthermore, wastewater also differs from one winery to another regarding its volume and composition and therefore is it vital for a detailed characterisation of the wastewater to fully understand the problem before managing it. However, prevention is better than cure. There are a number of winemaking practices that can help lower the volume of the wastewater produced to decrease the work load of the treatment system and increase the efficiency of treatment.